Validity and reliability of the Indonesian knowledge, attitude, and practice of allergic rhinitis questionnaire - Fakhriani, Rizka; Widuri, Asti; Amsriza, Fadli Robby; Daniswara, Deoni (Institute of Computer Science (IOCS), 2025)
Allergic rhinitis (AR) is a typical chronic condition commonly affecting the upper airway. Allergic rhinitis is marked by nasal congestion, rhinorrhea, pruritus, sneezing, and postnasal drip syndrome (PND), which includes eye itching and erythema. This study aims to assess the validity and reliability of the Indonesian version of the knowledge, attitude, and practice (KAP) of the allergic rhinitis questionnaire. The study employed a cross-sectional design. The study included patients with allergic rhinitis who were 18 or older and visited the otorhinolaryngology clinic between January and February 2024. The questionnaire was generated and disseminated using a Google form, and the statistical analysis was performed with SPSS 22.0. The correlation coefficient (r) between all questions on the knowledge dimension was consistently high, ranging from 0.302 to 0.828. The items on the attitude dimension had a strong positive association with the total score, as seen by the high correlation coefficients (all r = 0.962). The practice dimension also exhibited high correlation coefficients, ranging from 0.273 to 0.810 in total score. The questionnaire's validity and reliability have been established, confirming that the Indonesian version is recommended for future studies.